2020
DOI: 10.1109/access.2020.2993316
|View full text |Cite
|
Sign up to set email alerts
|

A Solution for the Full-Load Collection Vehicle Routing Problem With Multiple Trips and Demands: An Application in Beijing

Abstract: Municipal solid waste (MSW) collection has become a major challenge for clean city management and social sustainable development in developing economies. A new variant of the collection vehicle routing problem (CVRP) is addressed with the characteristics of full loads and multiple trips of the collection vehicles, and multiple demands of the garbage facilities, which is called the collection vehicle routing problem of the garbage facilities (CVRPGF) in this study. Dummy customers are introduced to equivalently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Later, in an experiment in a city in Tunisia, after ten iterations of the genetic algorithm, the running time was reduced from 15.2 to 10.91 h. After optimizing the genetic algorithm, the running time of the vehicle was reduced by 28.22% (Amal et al 2018 ). In addition, parallel annealing algorithms are also used to optimize vehicle collection paths (Zhang et al 2020 ). Using the parallel annealing algorithm to optimize the waste collection path in Xuanwu District, Beijing, Zhang et al ( 2020 ) found that the optimized scheme of the parallel annealing algorithm can reduce the time by 12% compared with the original scheme.…”
Section: Logistics Transportation and Recyclingmentioning
confidence: 99%
“…Later, in an experiment in a city in Tunisia, after ten iterations of the genetic algorithm, the running time was reduced from 15.2 to 10.91 h. After optimizing the genetic algorithm, the running time of the vehicle was reduced by 28.22% (Amal et al 2018 ). In addition, parallel annealing algorithms are also used to optimize vehicle collection paths (Zhang et al 2020 ). Using the parallel annealing algorithm to optimize the waste collection path in Xuanwu District, Beijing, Zhang et al ( 2020 ) found that the optimized scheme of the parallel annealing algorithm can reduce the time by 12% compared with the original scheme.…”
Section: Logistics Transportation and Recyclingmentioning
confidence: 99%
“…However, a sequence of collection tasks has not been considered in these studies. To alleviate this concern, an optimization problem is solved by using metaheuristics such that the number of collection trips is minimized [41]. The work [41] provides a theoretical model for a routing problem with the characteristics of full loads and multiple trips.…”
Section: Related Workmentioning
confidence: 99%
“…To alleviate this concern, an optimization problem is solved by using metaheuristics such that the number of collection trips is minimized [41]. The work [41] provides a theoretical model for a routing problem with the characteristics of full loads and multiple trips. A traveling salesman problem [42], as a combinatorial optimization problem, has been considered to model vehicle routing problems [43], [44].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, a restricted dynamic programming heuristic algorithm is proposed that finds the best solution for 32 out of 34 instances. Zhang et al equivalently transform the collection vehicle routing problem of the garbage facilities to the vehicle routing problem with simultaneous pickup-delivery and time windows by introducing dummy customers [29]. Besides, they propose a parallel simulated annealing algorithm to address the real application problem in the Xuanwu District of Beijing.…”
Section: B Vrppd Applications With Various Constraintsmentioning
confidence: 99%